Influence of trace zirconia addition on the properties of (K, Na)NbO3 solid solutions. Issue 23 (23rd May 2019) - Liu, Yi-Xuan; Thong, Hao-Cheng; Zhao, Chunlin; Liu, Qing; Xu, Xingyu; Wang, Ke; Li, Jing-Feng
Abstract : The missing understanding of the relationship between the properties and trace zirconia addition in KNN solid solutions is obtained. Abstract : The understanding of certain basic issues in (K, Na)NbO3 (KNN)-based systems is still missing, one of which being the influence of ZrO2 addition on the behaviors of KNN-based solid solutions at trace levels possibly introduced during the process of material preparation. Herein, KNN solid solutions with trace ZrO2 addition (0, 0.01, 0.05, and 0.1 mol%) were prepared by a normal sintering method. The dielectric permittivity and the piezoelectric coefficient d 33 reach the maximum ( ε r = 497 and d 33 = 139 pC N −1 ) with 0.1 mol% ZrO2 addition. Moreover, the microscopic results supported by PFM are in agreement with those from the macroscopic perspective. To establish the relationship among the ZrO2 addition contents, the induced defects and the properties of the solid solutions, a related defect model is proposed to support the experimental observation and the origin of induced defects is discussed. The results demonstrate that the properties of the KNN solid solutions can be closely affected by trace zirconia addition.